Resurgence of destructive behavior following differential rates of alternative reinforcement - Helvey, Casey Irwin; Fisher, Wayne W.; Greer, Brian D.; Fuhrman, Ashley M.; Mitteer, Daniel R. (Journal of applied behavior analysis, 2023)
Behavioral momentum theory (BMT) suggests that resurgence of destructive behavior may be at least partly determined by the rate of alternative reinforcement, with lean schedules of reinforcement producing less resurgence than dense schedules. Findings from basic and translational studies have been mixed, and the effects of alternative reinforcement rate on resurgence remain unclear. In the current study, we conducted a within‐subject evaluation of resurgence during extinction with four children following functional communication training using dense and lean (BMT‐informed) schedules of alternative reinforcement. We observed no reliable differences in resurgence across the dense and lean conditions. We discuss implications of these findings in relation to future research using quantitative analyses to evaluate the relative effects of alternative reinforcement rate and other BMT‐based strategies for mitigating resurgence in applied settings.